SINTESIS ASKORBIL LAURAT DARI METIL LAURAT DAN ASAM ASKORBAT MELALUI REAKSI TRANSESTERIFIKASI DENGAN KATALIS LIPASE SERTA UJI AKTIVITAS ANTIOKSIDAN - Dyah Adyana; Daniel Tarigan; Chairul Saleh (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2017)
Antioxidant are defined as compound that is capable of delay, postpone or prevent oxidation reaction, such as on foods and drugs. Antioxidant can be found in nature but the used is relatively limited because hydrophilic. This research aims to modified natural antioxidant so as be used in lipophilic media. Methyl laurate is one of a fatty acid ester potentialy can be used in industry. Modified were made by synthesize of methyl laurate and ascorbic acid through transesterification with catalyst is lipase from sesame seeds (Sesamun indicum L.) in a organic solvent such as acetone. Transesterification process does on reacton time at 36 hours at temperature (40-50) ºC and pH is 7 so has yield produced is 53,89 %. The result is ascorbyl laurate identified of the functional groups using by FT-IR spectrophotometer. Based on the result identification of the functional groups by FT-IR spectrophotometer, then do the analysis of antioxidant activity with a Radical Reduction Method DPPH (2,2-diphenyl-1-picrylhidrazyl). Antioxidant activity value IC50 is 40,57 ppm. This result indicated the potential of ascorbyl laurate as antioxidant.